KEMAMPUAN, PENGAWASAN DAN PRESTASI KERJA PETANI - Yuliyasni, Issri (Jurnal Ilmu Administrasi Negara, 2016)
Ability, and Job Performance Monitoring Farmers. The purpose of this study was to determine and analyze the influence factors and the ability to simultaneously control the work performance of rice farmers in the new venture farmer groups in Indragiri Hulu. The study population was as many as 42 members of farmer groups, all population sampled. Data were analyzed using multiple regression techniques. The results showed that the partial factors influence the ability of a significant and positive (0.332) on the work performance of farmers (Sig. 0.025 <0.05), and the control factor significant and positive impact (0.373) on the work performance of farmers (Sig. 0,023 <0, 05) Simultaneously with the R Square value above factors explain the magnitude of the ability of farmers and extension staff supervision on work performance farmer namely 29.7%, while the remaining 70.3% is influenced by other factors. Factors monitoring the ability of farmers and extension workers together have a significant effect (Sign value 0.001).